2019
DOI: 10.1021/acs.organomet.9b00156
|View full text |Cite
|
Sign up to set email alerts
|

Heteroditopic Ru(II)– and Ir(III)–NHC Complexes with Pendant 1,2,3-Triazole/Triazolylidene Groups: Stereoelectronic Impact on Transfer Hydrogenation of Unsaturated Compounds

Abstract: Imidazol-2-ylidene (ImNHC) and 1,2,3-traizol-5-ylidene (tzNHC) have been established as important classes of carbene ligands in homogeneous catalysis. To develop Ru(II)/Ir(III) complexes based on these ligand systems considering their electronic as well as steric profiles for hydride transfer reactions, we employed chelating ligands featuring combinations of ImNHC and triazole-N or mesoionic tzNHC donors bridged by a CH 2 spacer with possible modifications at triazole backbone. In general, synthesized Ru(II) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 99 publications
(41 reference statements)
2
19
0
Order By: Relevance
“…There are many means to achieve this transformation. For example, the reduction of imines, [ 2 ] the reductive amination of aldehydes, [ 3 ] the borrowing hydrogenation of alcohols and amines, [ 4 ] the reduction of amides, [ 5 ] the coupling of halogenated hydrocarbons [ 6 ] and boric acids [ 7 ] to amines, and the addition of amines and alkynes, [ 8 ] etc.…”
Section: Methodsmentioning
confidence: 99%
“…There are many means to achieve this transformation. For example, the reduction of imines, [ 2 ] the reductive amination of aldehydes, [ 3 ] the borrowing hydrogenation of alcohols and amines, [ 4 ] the reduction of amides, [ 5 ] the coupling of halogenated hydrocarbons [ 6 ] and boric acids [ 7 ] to amines, and the addition of amines and alkynes, [ 8 ] etc.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we reported Ru-NHC complexes as effective homogeneous catalysts for transfer hydrogenation and C–N bond-forming reactions, which revealed that the ancillary N -heterocyclic carbene (NHC) ligands enhance the activity of the Ru center . Inspired by these results, our interest in an atom-economic and inexpensive catalytic system prompted us to utilize the NHC ligand in a nickel-catalyzed N -alkylation reaction.…”
mentioning
confidence: 91%
“…Rare examples of pyrazole- and triazole-functionalized imidazole-2-ylidene-Ru(II) complexes were reported by the groups of Messerle [ 33 ], Kühn [ 34 ], and Rit [ 35 ]. Similarly to the pyridine-functionalized NHC complexes 17 – 20 , relatively modest activities were observed for the TH of acetophenone with the pyrazole derivatives 22a , 23 , and 24 that bear both a coordinated and an uncoordinated pyrazole moiety ( Figure 4 ).…”
Section: Transfer Hydrogenation Of Ketonesmentioning
confidence: 99%
“…The very modest activity observed with the hydride complex 24 , in particular, was surprising, as the pre-existing hydride ligand was expected to enable a more efficient TH reaction. The triazole derivatives 25 , 26 , and 27 proved slightly more active with maximum TON of 170, 168, and 500, respectively, under milder conditions, i.e., 0.1 ( 27 ) to 0.5 ( 25 , 26 ) mol% catalyst and only 5 ( 25 , 26 ) to 10 ( 27 ) mol% NaO i Pr or KO t Bu as base in isopropanol at reflux for 2–3 h [ 34 , 35 ]. It is noteworthy, however, that full conversion could not be attained in the cases of 25 and 26 under these conditions.…”
Section: Transfer Hydrogenation Of Ketonesmentioning
confidence: 99%